Penerapan Media Audio Visual Pada Materi Penjumlahan Kelas 2 Di SDN 3 Wonoboyo - Eka Saputra, Rizki (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2022)
Mathematics as a field of study taught in formal education institutions is an important part of efforts to improve the quality of education. Media is a tool for conveying internal information about the learning process, use of media, learning objectives that are expected to be more easily achieved compared to what was planned to be achieved previously. Audiovisual media is media that contains sound components and audio images. The type of research used is a qualitative research method. Here the researcher used a direct survey to make observations by interviewing one of the teachers by asking several questions regarding video-based audio-visual media for teaching mathematics for class 2 addition material at SDN 3 Wonoboyo so that the researcher could immediately get precise and accurate information. results. answers and results. By applying audio-visual media to class 2 addition material at SDN 3 Wonoboyo, it is able to increase students' enthusiasm for learning mathematics. Apart from that, the application of audio-visual media in addition to material can improve student learning outcomes.